Study Of The Behavioural Plasticity In Catla Catla: Response To Vedic Chant - Neetu Singh; Dinesh C. Sharma; Sumbul Zehra (Revista Electronica de Veterinaria, 2023)
This study investigates the behavioural adaptability of the freshwater fish Catla catla when exposed to the Vedic chant KRIMI NASHANA SUKTAM. The fish exhibited significant changes in behaviours such as feeding, crowding, movement, convulsions, opercular activity, shivering, lethargy, and scratching after treatment. Initially, erratic swimming and movement disruptions were observed, but the fish gradually adapted to the auditory stimulus, with stress-related behaviours like convulsions and shivering decreasing over time. Additionally, crowding and social behaviours became more pronounced. Previous research on other species, including koi carp and tilapia, similarly reported that auditory stimuli, such as music, can alter swimming patterns, feeding habits, and social interactions. These findings suggest that auditory stimuli, including Vedic chants, may act as environmental factors influencing fish behaviour, comparable to light and temperature. Although the results point to potential benefits of incorporating Vedic chants into aquaculture, further studies are needed to explore the mechanisms driving these behavioural changes and to assess the long-term effects on fish welfare.